The Role of Ismail Gasprali, Ali Bey Huseynzadeh and Yusif Akchura in the Formation of Political Panturkism - Najafov, Etibar (Scholarya Demo Journal of Ruby, 2020)
Ismail Gasprali, Ali bey Huseynzadeh and Yusif Akchura are founders of political Pan-Turkism. The political orientation of their Pan-Turkist activity was seen in defending political rights of the Turkic people, particularly in their struggle for elaboration of common literary language of the Turkic peoples, opening national schools, development of secular education, in their fighting against illiteracy, socio-economic and political backwardness of the Turkic peoples, in appealing to people for active participation in political life of society, in criticizing the policy of russification pursued by the Tsarist Russia, in propagating idea on borrowing scientific and technological achievements of the Western civilization.